Model-simulated net ecosystem Production (NEP) across the Mongolian Plateau - Chaoqun Lu (PANGAEA, 2019)
Here we used a well-evaluated process-based ecosystem model, Dynamic Land Ecosystem Model (DLEM), to simulate the spatial and temporal changes of net ecosystem productivity (NEP) in response to climate variability and extremes in the Mongolian Plateau from 1980 to 2010, at a spatial resolution of a quarter degree. The simulation period covers covering a drought period that spans from 2000 to 2009. In this study, we used time-series gridded data at a spatial resolution of quarter degree (about 30km at the equator) to describe key environmental changes in climate (warming and climate variability), land use, and atmospheric CO2 concentration, and nitrogen deposition in the Mongolian Plateau during 1901 to 2010. All the input data have been resampled to a quarter degree (about 30 km exttimes 30 km at the equator) and used to drive the DLEM model. After obtaining initial status, we set up two simulation experiments for the transient run: In experiment I (Climate), only climate drivers were allowed to change over time while other drivers were kept constant at the level of 1900; In experiment II (Climate plus Others), all the environmental drivers (including climate, land use, CO2 concentration, and nitrogen deposition) were turned on, by which we examine how climate and other input drivers together affected the direction and magnitude of C fluxes in the study region. Results from experiment II can be viewed as our "best estimate" of C dynamics in the Mongolian Plateau.
Supplement to: Lu, Chaoqun; Tian, Hanqin; Zhang, Jien; Yu, Zhen; Pan, Shufen; Dangal, Shree; Zhang, Bowen; Yang, Jia; Pederson, Niel; Hessl, Amy (2019): Severe long-lasting drought accelerated carbon depletion in the Mongolian Plateau. Geophysical Research Letters, Geophysical Research Letters, 46(10), 5303-5312, https://doi.org/10.1029/2018GL081418